IMPLEMENTATION OF QAWAâ€™ID FIQHIYYAH MUâ€™AMALAH ÙƒÙÙ„Ù‘Ù Ù‚ÙŽØ±Ù’Ø¶Ù Ø¬ÙŽØ±Ù‘ÙŽ Ù†ÙŽÙÙ’Ø¹Ù‹Ø§ ÙÙŽÙ‡ÙÙˆÙŽ Ø±ÙØ¨ÙŽØ§ ØÙŽØ±ÙŽÙ…ÙŒ ON AL- QARDHU AL- HASAN PRODUCTS IN SYARIâ€™AH BANKING - Basyirah, Luthfiana (Universitas Muhammadiyah Surabaya, 2021)
The source of Islamic law does not only come from the Al-Qur'an and Hadith, but also in ijma ', qiyas, istihsan, maslahah mursalah, istishab,' urf, syar'u man qablana, sadd asy-syari'ah. In addition, there is also an important foundation, namely qawa'id fiqhiyyah which serves as the basis for the formation of an Islamic law. Qawa'id fiqhiyyah is one of the laws that is universal and can be implemented in all its parts, so that it can be identified as the smallest part of a law. The main objectives of this study are to determine the relationship between qawa'id fiqhiyyah and Islamic banking, the implementation of qawa'id fiqhiyyah ÙƒÙÙ„Ù‘Ù Ù‚ÙŽØ±Ù’Ø¶Ù Ø¬ÙŽØ±Ù‘ÙŽ Ù†ÙŽÙÙ’Ø¹Ù‹Ø§ ÙÙŽÙ‡ÙÙˆÙŽ Ø±ÙØ¨ÙŽØ§ ØÙŽØ±ÙŽÙ…ÙŒ Â in al-qardhu al-hasan products in Islamic banking. This research uses a qualitative approach with descriptive research type. The results of the study state that: first, there is a link between qawa'id fiqhiyyah and Islamic banking because it functions to analyze the actual problem by establishing a law of various complex problems. Second, the implementation of qawa'id fiqhiyyah ÙƒÙÙ„Ù‘Ù Ù‚ÙŽØ±Ù’Ø¶Ù Ø¬ÙŽØ±Ù‘ÙŽ Ù†ÙŽÙÙ’Ø¹Ù‹Ø§ ÙÙŽÙ‡ÙÙˆÙŽ Ø±ÙØ¨ÙŽØ§ ØÙŽØ±ÙŽÙ…ÙŒ Â on al-qardhu al-hasan products is a good thing by eliminating the benefits of the product with a tathawwu 'contract or mutual assistance agreement, not a commercial transaction.